KINERJA OMBUDSMAN RI PERWAKILAN PROVINSI SULAWESI UTARA PADA PENYELESAIAN LAPORAN MASYARAKAT - TINDIGE, NANCY; Tampi, Johny Revo; LONDA, VERY (Sam Ratulangi University, 2019)
This study aims to analyze the performance of Ombudsman Republic of Indonesia representative of NorthSulawesi Province in the completion of public reports. The authors use the theory of Agus Dwiyanto aboutmeasuring organizational performance based on 3 of the 5 indicators, namely productivity,responsiveness, and responsibility. This study used a descriptive with a qualitative approach. Primary datafrom this study came from interviews, and the secondary data is document tracking. Data collectiontechniques are interviews, observation, and documentation. Data analysis techniques use data reduction,data presentation, conclusion and verification. The technique of checking the validity of data usingtriangulation. The result of this study showed that the performance of Ombudsman Republic of Indonesiarepresentative of North Sulawesi Province from the productivity indicator has been running optimallyseen from the achievement of the target of completion of the public report even though not supported byadecuate resource. Performance from the responsiveness indicator in terms of increasing publicparticipation by forming networks called â€œKawanua Ombudsmanâ€ has not gone well, while in respondingto public reports it has been going well. Performance from the responsibility indicator has been runningoptimally by following step by step in according to the existing rules.Keywords : Organizational Performance, Ombudsman